2013
DOI: 10.3164/jcbn.13-11
|View full text |Cite
|
Sign up to set email alerts
|

Extension of lifespan and protection against oxidative stress by an antioxidant herb mixture complex (KPG-7) in Caenorhabditis elegans

Abstract: Excessive generation of reactive oxygen species within cells results in oxidative stress. Furthermore, accumulation of reactive oxygen species has been shown to reduce cell longevity. Many dietary supplements are believed to have anti-aging effects. The herb mixture KPG-7 contains several components with antioxidant activity. We aim to clarify the mechanisms responsible for the antioxidant activity of KPG-7 and to establish whether KPG-7 has an anti-aging effect. We examined whether dietary supplementation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…A huge number of studies claiming a life lengthening effect of certain compounds/extracts have been published, most of which were purely descriptive, giving no indication regarding the underlying mechanisms, and thus always being at risk to measure a dietary restriction-like phenotype induced by the compound/extract under investigation [51,53]. Moreover, an antioxidant activity was supposed to underlie life-prolonging effects of various extracts [58,59], but this has to be interpreted cautiously, as the addition of non-enzymatic antioxidants appears to be mostly ineffective [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…A huge number of studies claiming a life lengthening effect of certain compounds/extracts have been published, most of which were purely descriptive, giving no indication regarding the underlying mechanisms, and thus always being at risk to measure a dietary restriction-like phenotype induced by the compound/extract under investigation [51,53]. Moreover, an antioxidant activity was supposed to underlie life-prolonging effects of various extracts [58,59], but this has to be interpreted cautiously, as the addition of non-enzymatic antioxidants appears to be mostly ineffective [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Studies with other compounds rich in polyphenols showed that they increased the lifespan and thermotolerance of C. elegans (Wilson et al, 2006;Pallauf et al, 2017). After studying the effect of an herbal mixture on C. elegans, Moriwaki et al (2013) concluded that the herbal mixture prolonged its lifespan, delayed aging, and also suppressed oxidation of protein cells in the nematode. However, it appears that the longevity of the C. elegans mev-1 (kn1) mutant produced by gallic acid, which is present in cauliflower, was not due to its antioxidant capacity but to its antimicrobial properties (Saul et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…ATP was extracted from SaOS-2 cells (Stanley, 1986;Moriwaki et al, 2013), and the concentration was subsequently determined by using the ATP luminescence kit (no. LL-100-1, Kinshiro, Toyo Ink, Japan).…”
Section: Determination Of Intracellular Atp Levelmentioning
confidence: 99%